The Location of Firms and General Spatial Price Equilibrium - John M. Hartwick (Queen's University, Department of Economics, 1970)
Alfred Weber (17) developed a model to show how a firm might locate when entering production given geographically distinct markets for the firm's product and the firm's inputs. The optimal location for the firm entering was shown to result from the solution to a straightforward transportation cost minimization problems. In a separate stream of development, Cournot (2) and Samuelson (13) demonstrated that a problem of economic rent maximization could define a set of prices and interpoint flows in space which characterised a spatial price equilibrium in reality. In this paper, I will indicate that Cournot-Samuelson principle of economic rent maximization and the extension to a dual problem in Hartwick (4) can be shown to generalize the Weber problem in a number of directions
Keywords: 330